Genotypic linkages of VP4, VP6, VP7, NSP4, NSP5 genes of rotaviruses circulating among children with acute gastroenteritis in Thailand - Pattara Khamrin (2018)
Rotavirus is the main cause of acute viral gastroenteritis in infants and young children worldwide. Surveillance of group A rotavirus has been conducted in Chiang Mai, Thailand since 1987 up to 2004 and those studies revealed that group A rotavirus was responsible for about 20-61% of diarrheal diseases in hospitalized cases. In this study, we reported the continuing surveillance of group A rotavirus in 2005 and found that group A rotavirus was detected in 43 out of 147 (29.3%) stool samples. Five different G and P genotype combinations were detected, G1P[8] (27 strains), G2P[4] (12 strains), G9P[8] (2 strains), G3P[8] (1 strain), and G3P[10] (1 strain). In addition, analysis of their genotypic linkages of G (VP7), P (VP4), I (VP6), E (NSP4), and H (NSP5) genotypes demonstrated that the rotaviruses circulating in Chiang Mai, Thailand carried 3 unique linkage patterns. The G1P[8], G3P[8], and G9P[8] strains carried their VP6, NSP4, NSP5 genotypes of I1, E1, H1, respectively. The G2P[4] strains were linked with I2, E2, H2 genotypes, while an uncommon G3P[10] genotype carried unique genotypes of I8, E3 and H6. These findings provide the overall picture of genotypic linkage data of rotavirus strains circulating in Chiang Mai, Thailand. © 2010 Elsevier B.V.